2022
DOI: 10.1002/pssr.202100636
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Low‐Energy Phases of Hafnia and Zirconia from Density Functional Theory Calculations

Abstract: A systematic simulation study of low‐energy phases of HfO2 and ZrO2, including 24‐atomic cells derived from 180° interphases, leads to a new monoclinic Pc phase (mIII) with a monoclinic angle and a polarization of 0.3 C m−2. This opens up a new transition path toward the monoclinic P2 1 /c phase (m) starting from the tetragonal P4 2 /nmc phase (t), with comparable lower‐energy barriers, where the high‐symmetric phases show the largest temperature dependence. The tetragonal P4 2 /nmc phase, the cubic (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…† Additionally, as mentioned in the introduction, first-principles calculations suggest the stability of other polar phases, including the Pc and Pmn2 1 phases. Although these phases have not been observed experimentally yet, the Pc phase was found to have low bulk energy, similar to the o phase in HfO 2 and ZrO 2 , 42 while the Pmn2 1 phase was found to have lower energy than the t phase in HfO 2 , 41,42 and higher energy in ZrO 2 . 42 The IR active phonon modes of these two phases were also calculated and are given in the ESI.…”
Section: Theoretical Ir Active Phonon Modesmentioning
confidence: 75%
See 2 more Smart Citations
“…† Additionally, as mentioned in the introduction, first-principles calculations suggest the stability of other polar phases, including the Pc and Pmn2 1 phases. Although these phases have not been observed experimentally yet, the Pc phase was found to have low bulk energy, similar to the o phase in HfO 2 and ZrO 2 , 42 while the Pmn2 1 phase was found to have lower energy than the t phase in HfO 2 , 41,42 and higher energy in ZrO 2 . 42 The IR active phonon modes of these two phases were also calculated and are given in the ESI.…”
Section: Theoretical Ir Active Phonon Modesmentioning
confidence: 75%
“…Although these phases have not been observed experimentally yet, the Pc phase was found to have low bulk energy, similar to the o phase in HfO 2 and ZrO 2 , 42 while the Pmn2 1 phase was found to have lower energy than the t phase in HfO 2 , 41,42 and higher energy in ZrO 2 . 42 The IR active phonon modes of these two phases were also calculated and are given in the ESI. † The simulated IR absorbance of ZrO 2 thin films reveals distinct differences between polar and non-polar phases, in contrast to XRD where most phases, especially the polar ones (Fig.…”
Section: Theoretical Ir Active Phonon Modesmentioning
confidence: 75%
See 1 more Smart Citation
“…For instance, the diluted magnetism could only appear in the t-phase for undoped ZrO 2 thin films [22]. Recently, the ferroelectricity has also been studied in ZrO 2 films [23][24][25]. For instance, Silva et al [23] reported an unprecedented ferroelectric structure in pure ZrO 2 thin films, opening up a new route to ferroelectric devices using Zr-rich HZO.…”
Section: Introduction mentioning
confidence: 99%
“…[22,38,39] This phase is also found to be energetically close to the ground state mphase. [39,40] Additionally, the t-phase has been identified as a potential driver of antiferroelectric behavior in ZrO 2 polycrystalline thin films [41] ; this has been explained as a transition from the nonpolar t-phase to the polar o-phase. [41] This second approach is the most commonly adopted in the literature.…”
Section: Introductionmentioning
confidence: 99%